Feathers, eggs, and blood as bioindicators of heavy metals and their impact on DNA damage in captive Pavo cristatus - Shabana Naz; Sania Satti; Alina Razzaq; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Sina Gul (Journal of Applied Animal Research, 2023)
Heavy metals and their genotoxic effects in captive Indian Peafowl (Pavo cristatus) residing in various regions of Punjab, Pakistan, specifically, Wildlife Park Bahawalpur (WPB), Jallo Wildlife Park Lahore (JWPL), and Wildlife Park Murree (WPM) were evaluated in blood, feathers, eggshell and egg content samples. The Single-cell gel electrophoresis (Comet) assay was performed to evaluate DNA damage. The results showed that the concentration of Cr was significantly high (P < 0.05) in Blood (3.79 µg/g), Feather (4.87 µg/g), Egg shell (51.02 µg/g) and Egg Content (13.59 µg/g) samples of Jallo Wildlife Park Lahore followed by Pb, Mn, Ni and Co. The highest (P < 0.05) metal accumulation was found in eggshell samples due to its porous structure as compared to other samples. Likewise region-wise analysis showed that Jallo Wildlife Park Lahore appeared to be more polluted than WPB and WPM. Indian Peafowl kept at WPM and JWPL exhibited higher levels of genotoxicity compared to the birds kept at WPB. This disparity can be attributed to the increased exposure to pollution and heightened stress experienced by the peafowl in the former two locations. This study concluded that among all the three study sites of Punjab, the WPB is most suitable for housing captive animals and birds.